PENGARUH ENTREPRENEURIAL KNOWLEDGE, ENTREPRENEURIAL MOTIVATION, FAMILY SUPPORT, DAN EMOTIONAL INTELLIGENCE TERHADAP ENTREPRENEURIAL INTENTION - Putra, Deko Rhama; Prabandari , Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Unemployment is a crucial problem for economic growth and development in Indonesia. The solution for it is increasing the quantity of jobs by, one of which, boosting the number of both small and large companies. Therefore, fostering entrepreneurial intention is a way out to reduce unemployment in Indonesia. The objective of this research is to identify the effects of entrepreneurial knowledge, entrepreneurial motivation, family support, and emotional intelligence on entrepreneurial intention by taking Indonesian university students as the case study. The research location is campuses in Indonesia, from which 230 people were selected as the respondents. The data was analyzed using multiple linear regression in SPSS version 24. This study finds that entrepreneurial knowledge, entrepreneurial motivation, family support, and emotional intelligence significantly influence entrepreneurial intention. Therefore, the higher the entrepreneurial knowledge, entrepreneurial motivation, family support, and emotional intelligence, the higher Indonesian university students’ entrepreneurial intention.